Carboxymethyl cellulose films derived from pineapple waste: Fabrication and properties - Heru Suryanto; Daimon Syukri; Anni Faridah; Uun Yanuhar; Joseph Selvi Binoj; Fajar Nusantara; Komarudin Komarudin; Ulfieda Anwar Ulhaq (Universitas Muhammadiyah Magelang, 2025)
Plastic waste poses a significant environmental challenge due to its non-biodegradable nature, emphasizing the need for sustainable alternatives like bioplastics from natural resources. This study develops and characterizes bioplastic films made from carboxymethyl cellulose (CMC) derived from bacterial cellulose synthesized using pineapple biowaste. Pineapple waste underwent fermentation to produce bacterial cellulose, which was chemically modified into CMC. Films were fabricated using CMC solutions with varying glycerol concentrations (0.5%, 1.0%, 1.5%, and 2.5% v/v). Characterization techniques, including SEM, XRD, FTIR, TGA, mechanical testing, and antibacterial assays, revealed that increasing glycerol concentrations smoothed the film's cross-sectional morphology, reduced crystallinity, and altered functional groups (e.g., new peaks at 870 cm⁻¹ and 935 cm⁻¹ attributed to C–H deformation). TGA indicated a four-stage thermal degradation pattern, with mass loss increasing from 77.2% to 88.4% at 2.5% glycerol, reflecting enhanced plasticization. Mechanical testing showed that the highest glycerol concentration increased film flexibility by 40.7 times while reducing tensile strength by 89.7%. Antibacterial activity against E. coli and S. aureus also improved with glycerol content. These results demonstrate the potential of CMC-based bioplastic films as sustainable packaging materials, offering customizable properties and promoting the value-added use of agricultural waste.